2005
DOI: 10.1021/jf051504p
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Extraction of Ginsenosides from American Ginseng (Panax quinquefolius L.) for High-Performance Liquid Chromatography−Ultraviolet Analysis

Abstract: Four methods were tested for extraction and recovery of six major ginsenosides (Rb1, Rb2, Rc, Rd, Re, and Rg1) found in roots of American ginseng (Panax quinquefolius): method A, sonication in 100% methanol (MeOH) at room temperature (rt); method B, sonication in 70% aqueous MeOH at rt; method C, water extraction (90 degrees C) with gentle agitation; and method D, refluxing (60 degrees C) in 100% MeOH. After 0.5-1 h, the samples were filtered and analyzed by high-performance liquid chromatography (HPLC)-UV. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Rg1 extraction by sonication in methanol has been proved to be an effective method reported by Chen et al (2000) and Corbit et al (2005). The modification in our report was that condensation of the condensation of Rg1 extract was achieved by nitrogen flowing at room temperature after sonication.…”
Section: Recoverymentioning
confidence: 77%
“…Rg1 extraction by sonication in methanol has been proved to be an effective method reported by Chen et al (2000) and Corbit et al (2005). The modification in our report was that condensation of the condensation of Rg1 extract was achieved by nitrogen flowing at room temperature after sonication.…”
Section: Recoverymentioning
confidence: 77%
“…The estrogenic ginsenoside Rb1 is one of the most abundant ginsenosides found in methanol-extracted P quinquefolium root. 26,37 In the interpretation of results, it is also important to consider the influence of working with whole root extracts containing a mixture of approximately 20 ginsenosides that may have variable effects on cellular events depending on their individual concentrations, as well as cell culture conditions. At low concentrations of alc-GE, the net effect of the individually acting ginsenosides is an estrogenic response, possibly due to some estrogenic ginsenosides directly binding to ERs and others stimulating estrogenic responses independent of ER binding.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Most ginsenosides are soluble in aqueous alcohols, and alcohol-extracted ginseng contains greater ginsenoside concentrations than water onlyextracted ginseng does. 26 Thus, the processing method of the ginseng used in scientific study, as well as ginseng supplements, may account for reported differences in laboratory results. The goal of the present study was to determine the effects of alcohol-and water-extracted P quinquefolium root on human breast cancer cell proliferation, as well as to assess the involvement of estrogen receptors.…”
mentioning
confidence: 99%
“…The HWEG was tested using the E-TOXATE detection kit (Sigma-Aldrich; St. Louis, MO) to verify that bacterial endotoxin was not present. The final endotoxin-free HWEG was analyzed for presence and concentration of ginsenosides using high-performance liquid chromatography as reported elsewhere (Corbit et al, 2005). Lyophilized products were analyzed for ginsenoside content by HPLC (Corbit et al, 2005), total carbohydrate content by phenol-sulfuric method (Masuko et al, 2005), glycosyl composition by gas chromatography-mass spectrometry (King and Murphy, 2009), and protein content by BCA assay (Thermo Pierce; Rockford, IL).…”
Section: Ginseng Preparations Analysis and Dosingmentioning
confidence: 99%
“…The final endotoxin-free HWEG was analyzed for presence and concentration of ginsenosides using high-performance liquid chromatography as reported elsewhere (Corbit et al, 2005). Lyophilized products were analyzed for ginsenoside content by HPLC (Corbit et al, 2005), total carbohydrate content by phenol-sulfuric method (Masuko et al, 2005), glycosyl composition by gas chromatography-mass spectrometry (King and Murphy, 2009), and protein content by BCA assay (Thermo Pierce; Rockford, IL). The extract contained 6.89% (w/w) ginsenosides, a total carbohydrate content of 92% (w/w) (consisting of 99.3% glucose, 0.3% arabinose, 0.2% galactose, and 0.1% rhamnose), and a total protein content of less than 3.0%.…”
Section: Ginseng Preparations Analysis and Dosingmentioning
confidence: 99%